Influence of high-intensity horizontal mould vibration on the density, grain refinement and mechanical characteristics of a die cast aluminium alloy (LM21). (June 2023) - Yadav, Siddharth; Kumar, Santosh; Tewari, Satya Prakash; Ram, Subhash Chandra; Prasad, Rabindra; Sinha, Nitesh Kumar; Deo, Manish; Singh, Jayant Kumar
The present investigation analysed the effect of mould vibration using an indigenous vibrating setup on the physical, metallurgical and mechanical properties of die cast A308 alloy. The alloy was vibrated at a constant amplitude of 31µm at 75, 100, 125 and 150 Hz. The work aims to generate more nucleation sites during melt solidification by fragmenting dendrites and Si particles. To examine the changes in metallurgical characteristics, α-Al, secondary dendritic arm spacing, length, width and aspect ratio of eutectic Si particles were studied using optical microscopy, scanning electron microscopy and X-ray diffraction analysis. It was observed that the size of α-Al, secondary dendritic arm spacing, length, width and aspect ratio of eutectic Si particles were decreased by 47%, 53%, 65%, 12% and 61%, respectively. Whereas, the shape factor and density of the alloy were enhanced by 25% and 1.62% compared to stationary cast samples because of mechanical vibration treatment at an optimum frequency of 100 Hz. Mechanical testing findings demonstrated a 13%, 20%, 15% and 20% increase in the parameters such as yield strength, ultimate tensile strength, percentage elongation and microhardness at 100 Hz when compared to the stationary cast sample. Grain refinement, uniformity of structure, improvement in the morphology of metallurgical characteristics, decreased porosities and subsequent increase in density were all factors that contributed to the improvement. Tensile test samples with scanning electron microscopy fractography demonstrated transgranular brittle fracture and a few ductile rips.